2022
DOI: 10.1038/s41598-022-22242-9
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic process and tutorial of the African buffalo optimization

Abstract: This paper presents the data description of the African buffalo optimization algorithm (ABO). ABO is a recently-designed optimization algorithm that is inspired by the migrant behaviour of African buffalos in the vast African landscape. Organizing their large herds that could be over a thousand buffalos using just two principal sounds, the /maaa/ and the /waaa/ calls present a good foundation for the development of an optimization algorithm. Since elaborate descriptions of the manual workings of optimization a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…It is important to keep in mind that developing the tests and setting up the SAS are not simple tasks, and they may cost money. The authors want to extend their future work by utilizing the optimization strategies indicated in the research of other scholars [39][40][41][42][43][44][45][46][47]. Data Availability Statement: Data will be available upon reasonable request.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to keep in mind that developing the tests and setting up the SAS are not simple tasks, and they may cost money. The authors want to extend their future work by utilizing the optimization strategies indicated in the research of other scholars [39][40][41][42][43][44][45][46][47]. Data Availability Statement: Data will be available upon reasonable request.…”
Section: Discussionmentioning
confidence: 99%
“…The coordinated scheduling of BESSs and MT unit for maximizing DPF is a complex non-linear multi-constraint optimization problem which can't be solved by employing conventional optimization techniques. Such complex combinatorial optimization problems can be solved by using AI-based natureinspired meta-heuristic or evolutionary techniques which may include genetic algorithm (GA) [40], gravitational search algorithm (GSA) [41,42], fireworks algorithm (FWA) [32], African buffalo optimization (ABO) [23,24] and many more. The ABO algorithm was first developed by Odili et al in 2015 [43].…”
Section: Solution Methodology For Coordinated Schedulingmentioning
confidence: 99%
“…For further details like basic steps, proposed modifications in standard variant, mathematical equations, and algorithm parameters' of MABO the readers may refer to refs. [23,24,43]. The structure of an individual buffalo is composed of decision variables of the optimization problem.…”
Section: Solution Methodology For Coordinated Schedulingmentioning
confidence: 99%
See 1 more Smart Citation
“…Since thousands of executions can be adopted by search-based approaches to be effective and successful, this can be considered an achievement of the approach [41]. For future work, the authors want to extend their research using the optimization techniques mentioned in the research work of different researchers [60][61][62][63][64][65][66][67][68][69]. The concept should be examined in the future through different experiments with a considerably larger number of feature models, to compare them with those used in our proposed work.…”
Section: Threats To Validitymentioning
confidence: 99%